Analisa Koordinasi Proteksi Feeder Lakarsantri pada Transformator II 50 MVA GIS Karangpilang - Reza Sarwo Widagdo; Gatut Budiono; Hadi Tasmono (Jurnal FORTECH, 2021)
In the event of a short circuit interruption it is still very worrying where there are still many problems with protection equipment that does not work properly. In field conditions, the transformer at GIS Karangpilang often fails to disconnect the feeder. Based on this incident, it will be discussed how to coordinate the relay between incoming and Lakarsantri feeders. The calculation results from the working time of the relay feeder are 0.3 seconds with the working time on the incoming part being 0.68 seconds. Based on data from GIS Karangpilang, the working time of the relay in the feeder section was 0.41 seconds and 0.69 seconds in the incoming section with a fault current of 4.5 kA showing good results. In the short circuit simulation results, the manual calculation data and the data obtained from the Karangpilang GIS are not much different, where the working time of the relay feeder is 0.11 seconds faster than the incoming working time, with a time of 0.7 seconds which is in accordance with the relay settings.